Pindah Agama Setelah Perkawinan Perspektif Kompilasi Hukum Islam - Brillian Sabila Anjani Putri; Abdurrrahman Satu; Amar Multazam; Brilliana Fajrin Izza Zain; Hasan Husin; Royanis Ansory; Muhibur Rohman Atoilah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
Extrajudicial divorce (talak siri) remains prevalent within Indonesian Muslim society and poses significant legal challenges due to its incompatibility with the national family law system, particularly in terms of legal certainty, protection of women’s and children’s rights, and orderly population administration. This study aims to analyze the normative differences between Islamic jurisprudence (fiqh) and Indonesian positive law concerning talak siri practices and to examine their legal implications. Employing a normative legal research method with statutory, conceptual, and comparative approaches, this study examines fiqh doctrines, Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law, and relevant legal doctrines related to divorce. The findings reveal a fundamental disparity between the validity of divorce under fiqh and its recognition under Indonesian state law, resulting in dual marital status and legal uncertainty that adversely affect the civil rights of former wives and children, particularly regarding marital status, inheritance, and administrative recognition. This study highlights isbat cerai as a crucial juridical mechanism to bridge normative differences, ensure legal certainty, protect vulnerable parties, and maintain orderly population administration.